2017
DOI: 10.1247/csf.17019
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Ror2 Associated with Fibrosis of the Submandibular Gland

Abstract: The submandibular gland (SMG) is one of the major salivary glands that play important roles for variety of physiological functions, such as digestion of foods, prevention of infection, and lubrication of the mouth. Dysfunction of the SMG, often associated with a salivary inflammation, adversely influences a person's quality of life. However, the mechanism underlying inflammation-driven dysfunction of the SMG is largely unknown. Here, we used a mouse model in which the main excretory duct of the SMG is ligated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Clinical samples of human chronic obstructive sialadenitis have been found to express TGF-β [116,117]. Mice models with intentional ductal ligation in salivary glands showed robust expression of TGF-β1, 3 and TGFβR1, but not TGF-β2 [118,119]. The use of exogenous TGFβR1 inhibitor in the mice model reduced fibrotic markers in ligation-induced salivary gland injury [119].…”
Section: Sialadenitismentioning
confidence: 99%
“…Clinical samples of human chronic obstructive sialadenitis have been found to express TGF-β [116,117]. Mice models with intentional ductal ligation in salivary glands showed robust expression of TGF-β1, 3 and TGFβR1, but not TGF-β2 [118,119]. The use of exogenous TGFβR1 inhibitor in the mice model reduced fibrotic markers in ligation-induced salivary gland injury [119].…”
Section: Sialadenitismentioning
confidence: 99%
“…Following more in-depth research, ror2 was shown to be highly expressed in a variety of cancer tissues and correlated with patient prognosis (36)(37)(38). Studies have reported that Wnt5a-ror2 signaling is involved in the regulation of inflammatory diseases, such as atherosclerosis, and Ror2 is highly expressed in atherosclerotic plaques and atherosclerotic patient sera, similar to Wnt5a (20,27,39). These findings suggested that Ror2 may regulate the development of aS.…”
Section: Discussionmentioning
confidence: 83%
“…Importantly, however, expression of Ror2 and Ror1 was also detectable at apparent and marginal levels, respectively, in noninvasive, dysplastic pleural mesothelial cells within the MPM specimens (Supporting information Figure S1b), probably associated with asbestos-induced chronic inflammation. In fact, expression of Ror1 and Ror2 has been shown to be induced during tissue damage-induced inflammatory responses in adult tissues (Endo et al, 2017;Kamizaki et al, 2017;Li et al, 2013;Takahashi et al, 2017). These findings suggest that Ror1 and Ror2 might be involved in initiation and progression of MPM associated with chronic inflammation and could be novel molecular markers for MPM.…”
Section: Expression Of Ror1 and Ror2 In Clinical Specimens And Cellmentioning
confidence: 90%
“…Neither Ror1 nor Ror2 was detected in normal lung tissues (Supporting information Figure S1a) and desmoplastic stroma ( Figure 1a) adjacent to the epithelioid and sarcomatoid tumors, respectively. In fact, expression of Ror1 and Ror2 has been shown to be induced during tissue damage-induced inflammatory responses in adult tissues (Endo et al, 2017;Kamizaki et al, 2017;Li et al, 2013;Takahashi et al, 2017). In fact, expression of Ror1 and Ror2 has been shown to be induced during tissue damage-induced inflammatory responses in adult tissues (Endo et al, 2017;Kamizaki et al, 2017;Li et al, 2013;Takahashi et al, 2017).…”
Section: Expression Of Ror1 and Ror2 In Clinical Specimens And Cellmentioning
confidence: 99%